Exploring the Nutritional Potential of Spent Coffee Grounds as a Substitute for Rice Bran in Feeds for Nile tilapia, Oreochromis niloticus: An Evaluation of Growth Performance and Biological Indices - Wikit Phinrub; Sontaya Sookying; Phanit Srisuttha; Nantaporn Sutthi; Paiboon Panase (Aquaculture Nutrition)
This study aimed to assess the viability of replacing rice bran with spent coffee grounds (SCG) in the diets of Oreochromis niloticus (average body weight, 48.8 ± 0.42 g). The fish were randomly allocated into four sets of three groups each and placed in net cages (1 m × 2 m × 0.5 m) at a density of 30 fish per cage. They were fed diets with four different replacement levels: 0%, 5%, 10%, and 15% of SCG over a period of 90 days. Growth and serum biochemical indices were monitored three times at 30, 60, and 90 days. During the experiment, there were no significant differences (P >0.05) observed in growth indices, including weight gain (WG), daily WG, specific growth rate, feed conversion rate, protein efficiency ratio, and survival rate among the groups at 30, 60, and 90 days. Serum biochemical indices, such as aspartate aminotransferase and alanine aminotransferase, showed a similar trend with significant differences observed only on day 30, while the lowest and highest levels were found in the control and 15% SCG replacement groups, respectively. For total cholesterol, a significantly different result was found only on day 30. However, these differences were not sustained in subsequent assessments. Conversely, serum glucose, total protein, albumin, and globulin remained unaffected by SCG replacement throughout the experiment. The findings indicate that replacing rice bran with up to 15% SCG did not adversely impact the growth performance or key serum biochemical indices of Nile tilapia. To the researchers’ knowledge, these findings are the first in the field to substitute SCG for rice bran, opening a new avenue for further research.